Subject‐specific models of susceptibility‐induced B0 field variations in breast MRI. Issue 1 (3rd August 2012) - Jordan, Caroline D.; Daniel, Bruce L.; Koch, Kevin M.; Yu, Huanzhou; Conolly, Steve; Hargreaves, Brian A.
Abstract Purpose: To rapidly calculate and validate subject‐specific field maps based on the three‐dimensional shape of the bilateral breast volume. Materials and Methods: Ten healthy female volunteers were scanned at 3 Tesla using a multi‐echo sequence that provides water, fat, in‐phase, out‐of‐phase, and field map images. A shape‐specific binary mask was automatically generated to calculate a computed field map using a dipole field model. The measured and computed field maps were compared by visualizing the spatial distribution of the difference field map, the mean absolute error, and the 80% distribution widths of frequency histograms. Results: The 10 computed field maps had a mean absolute error of 38 Hz (0.29 ppm) compared with the measured field maps. The average 80% distribution widths for the histograms of all of the computed, measured, and difference field maps are 205 Hz, 233 Hz, and 120 Hz, respectively. Conclusion: The computed field maps had substantial overall agreement with the measured field maps, indicating that breast MRI field maps can be computed based on the air–tissue interfaces. These estimates may provide a predictive model for field variations and thus have the potential to improve applications in breast MRI. J. Magn. Reson. Imaging 2013;37:227–232. © 2012 Wiley Periodicals, Inc.